Proses Pembelajaran Selama Pandemi Covid-19 di SDN 45 Mulaeno Kabupaten Bombana - Ana Susyana; Aisyah Mu'min (Diniyah: Jurnal Pendidikan Dasar, 2021)
As a result of the spread of Covid-19, learning in primary schools must be done online. This learning system appears to be new for teachers and students, so it raises a lot of problems and polemics. The purposes of this study are to examine the learning process during the COVID-19 pandemic at SDN 45 Mulaeno and to find out how the teachers evaluate students’ performance at the school. This study employed qualitative research with observations, interviews, and document studies as data collection techniques. The data were then analyzed through the stages of data collection, data presentation, and drawing conclusion. The results showed that during the pandemic, learning at SDN 45 Mulaeno was still carried out face-to-face but with a limited time. In the face-to-face meeting, the teacher only gives assignments to students to do at their homes. Evaluation of student learning development was carried out by looking at the number of tasks that have been done by students for the affective and psychomotor aspects, and accumulating the value of these assignments for the cognitive aspects.Keywords: Learning during the pandemic, evaluation technic, elementary school